Realization basic directions of the Bologna process in preparation of teachers physical cultures in Polish Institutes of higher - Pasichnik V.R (Kharkov National Pedagogical University, 2010)
Basic progress of higher school trends are presented in Poland. Directions of introduction of decisions of Bologna declaration and European educational standards are considered in preparation of teachers of physical culture. Information is resulted about the improvement of process of preparation of specialists of physical education and sport in the Warsaw academy of physical education. Growth of the state financing of research projects and introduction of the European educational projects is marked. It renders assistance to perfection of process of training of pedagogical personnels.